Theoretical and methodological challenges for teaching education policies in the historical materialist perspective - Marcela Alejandra Pronko (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2016)
This paper contains some reflections that resulted from a long experience in curriculum components related to educational policies in undergraduate and graduate programs in Argentina and Brazil. These reflections are a first systematization, without any claim to completeness, of the main problems identified in the end-of-course works prepared by students from three curriculum components, distinguishing general problems, resulting from deficiencies of these students‟ previous education, from specific issues related to difficulties in understanding the conceptual basis of the historical materialism and the theoretical-methodological conception that guides the organization of these courses. After a brief presentation of these bases, this text highlights and discusses four very common problematic conceptions in these final works: a history with no subject, which renews the myth of progress; a world that is driven almost exclusively by ideas, transformed into pure political will; a State that assuming the central role in the social scene is understood as a subject; an education as an isolated sphere of reality. Finally, the brief closing remarks point out paths to deepen the proposed reflection.